2012
DOI: 10.5194/nhess-12-2753-2012
|View full text |Cite
|
Sign up to set email alerts
|

Fire cue effects on seed germination of six species of northwestern Patagonian grasslands

Abstract: Abstract. Postfire recruitment of seedlings has been attributed to a stimulation of germination by fire-related cues. The germination response to heat shock (80 • C -5 min), smoke (60 min), the combination of both factors and no heat no smoke (control) was studied in six native species (two dominant grasses, two dominant shrubs and two annual fugitive herbs) of northwestern Patagonian grasslands. Seeds of the grasses Festuca pallescens and Stipa speciosa and the shrub Senecio bracteolatus (Asteraceae) germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
2
16
2
1
Order By: Relevance
“…Moreover, when this species was subjected to experimental burning, seedling growth decreased (Franzese and Ghermandi 2012). The germination of F. pallescens was not affected by smoke, heat, or the combination of these factors (Gonzalez and Ghermandi 2012), but experimental burning was shown to reduce the germination and seedling growth of this species (Franzese and Ghermandi 2012). Even though P. speciosa and F. pallescens can resprout after fires, the remaining biomass is very low, and as these species are constantly subjected to grazing, especially by sheep, seedlings and young resprouts can be rapidly eliminated.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, when this species was subjected to experimental burning, seedling growth decreased (Franzese and Ghermandi 2012). The germination of F. pallescens was not affected by smoke, heat, or the combination of these factors (Gonzalez and Ghermandi 2012), but experimental burning was shown to reduce the germination and seedling growth of this species (Franzese and Ghermandi 2012). Even though P. speciosa and F. pallescens can resprout after fires, the remaining biomass is very low, and as these species are constantly subjected to grazing, especially by sheep, seedlings and young resprouts can be rapidly eliminated.…”
Section: Discussionmentioning
confidence: 90%
“…The shrubs M. spinosum and S. bracteolatus are present in low density and are scattered within the grassland matrix. After exposure to fire cues, seeds from M. spinosum were killed and germination of S. bracteolatus seeds was inhibited (Gonzalez and Ghermandi 2012). P. speciosa seeds were shown to increase germination after being exposed to smoke alone (Franzese and Ghermandi 2012) but when the seeds were exposed to a combination of heat and smoke, germination was inhibited (Gonzalez and Ghermandi 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species forms a transient seed bank: seeds of S. bracteolatus are not found in the seed bank after fire (Gonzalez and Ghermandi 2008). Also seed germination is not stimulated by heat (808C) and smoke treatments (Gonzalez and Ghermandi 2012). Further, Franzese (2006) found that seed production of S. bracteolatus was greater in burned than unburned grasslands 5-6 years after fire.…”
Section: Introductionmentioning
confidence: 99%